Russian Federation : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper on the Russian Federation underlies inflation persistence and evolution in response to structural shocks. Inflation in Russia has been characterized by a considerable degree of persistence. An explicit inflation-targeting framework may help reduce firms' uncertainty about the future. This, in turn, may allow firms to be more forward-looking, thereby reducing persistence. The exchange rate is the Central Bank of Russia's (CBR) main policy instrument for controlling inflation. Allowing more nominal appreciation would help to keep inflation on a downward path and better anchor inflation expectations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet